Primary prevention for acute kidney injury in ambulatory patients (2020)
Acute kidney injury (AKI) is a heterogeneous group of conditions characterized by a sudden decrease in glomerular filtration rate (GFR), which usually induces the accumulation of nitrogenous-waste substances in the blood. It is expressed as an increase in serum creatinine levels (≥ 0.3 mg/dl within 48 hours or ≥1.5 times from baseline within the previous 7 days) or by a urine volume reduction of ˂0.5 ml/kg/h in 6 hours [1]. AKI is a relevant condition since it is usually associated with 1–7% and 30–50% of hospital and intensive care unit (ICU) admissions, respectively; showing a significant morbidity-mortality rate, and progression to chronic kidney disease (CKD) [1–7]. Even though many strategies have been proposed to achieve an early AKI diagnosis (e.g. novel biomarkers, informatics alarms), and an AKI effective treatment (e.g. renal protective drugs, biocompatible renal replacement therapies), both objectives remain unachieved; therefore, AKI prevention is currently the best ‘therapeutic’ strategy for this condition.